Deviation from Optimal Capital Structure and Inefficiencies of Investment - Fatemeh Soheilyfar (Shahid Bahonar University of Kerman, 2020)
Objective: Investment efficiency is one important factor affecting a firm's performance. Also, financing decisions affect investment decisions, regarding the effects of the non-optimal capital structure on the rate of capital cost and cash flows of the firm. This study examines the relationship between deviation from optimal capital structure and inefficiency of investment. Methods: This is a descriptive, correlation, and post-event study. The statistical population consists of the companies listed in the Tehran Stock Exchange, and the sample comprises 142 companies during 2007-2017, accounting for 1562 company-years. Results: The findings showed that an increase in the deviation from optimal capital structure increases investment inefficiency.  Also, an increase in the positive deviation from optimal capital structure (over-leveraged) has a significant and negative effect on over-investment and a positive effect on under-investment. Besides, an increase in the negative deviation from optimal capital structure (under-leveraged) has a significant and positive effect on over-investment and negative effect on under-investment. Conclusion: The results imply that the optimal capital structure can affect investment efficiency by moderating the cash flow availability and the expected interest rate.